PENERAPAN MEDIA STRIP STORY DALAM MENINGKATKAN MAHARAH AL-QIRA’AH SISWA KELAS VIII.B SMP PEST PUTRI YATAMA MANDIRI GOWA - Syarif, Nurul Rezkyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to implement strip story media in Arabic language learning, specifically in enhancing mahārah al-qirā’ah (reading skills), to analyze the effectiveness of this media in improving students’ reading abilities, and to identify the supporting and inhibiting factors in its implementation. This research employed a Classroom Action Research (CAR) approach conducted in two cycles. The research subjects were 29 students of class VIII B at SMP Pest Putri Yatama Mandiri Gowa. Data collection techniques included observation, interviews, documentation, and tests. The results of the study showed that the use of strip story media significantly improved students’ reading skills, as indicated by the increase in the percentage of students achieving the minimum mastery criteria (KKM) from 20.7% (pre-cycle) to 65.5% (Cycle I) and 86.2% (Cycle II). Moreover, the use of this media also enhanced students’ motivation and active participation during the learning process.